Analisis Penerapan Sistem Informasi Manajemen Kepegawaian (SIMPEG) dalam Pengelolaan Administrasi Kepegawaian pada Lapas Perempuan Kelas III Mamuju - Irma; Syariah Alfadila Mirsan; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
The implementation of the Personnel Management Information System (SIMPEG) represents a strategic initiative to enhance efficiency, accuracy, and accountability in personnel administration, particularly within government institutions such as the Women’s Correctional Facility Class III Mamuju. SIMPEG plays a crucial role in supporting integrated personnel data management, including employee records, career history, position tracking, and performance evaluation. This article aims to provide an in-depth analysis of SIMPEG implementation by examining its functions, benefits, challenges, and overall effectiveness in supporting personnel management. This study also investigates various factors that influence the success of SIMPEG implementation, encompassing both facilitating and inhibiting elements. The findings indicate that SIMPEG has contributed positively to accelerating administrative processes, improving data accuracy, and enhancing transparency in personnel-related decision-making. However, the system has not yet reached its optimal potential due to several constraints, including limited human resource competencies, inadequate network infrastructure, and inconsistencies in regular data updates. Therefore, continuous improvement efforts are necessary, particularly in the form of user capacity development through targeted training programs, strengthening information technology infrastructure, and conducting regular system monitoring and evaluation. With these measures in place, SIMPEG is expected to deliver more substantial benefits and support the establishment of a professional, efficient, and accountable personnel management system within government organizations.